Tranexamic acid at cesarean delivery: drug‐error deaths. (27th October 2022) - Moran, Neil F.; Bishop, David G.; Fawcus, Susan; Morris, Edward; Shakur‐Still, Haleema; Devall, Adam J.; Gallos, Ioannis D.; Widmer, Mariana; Oladapo, Olufemi T.; Coomarasamy, Arri; Hofmeyr, G. Justus
Abstract: The use of tranexamic acid for postpartum hemorrhage has entered obstetrical practice globally with the evidence‐based expectation of saving lives. This improvement in the care of women with postpartum hemorrhage has come at a price. For the anesthetist, having tranexamic acid ampoules close at hand would seem an obvious strategy to facilitate its use during cesarean delivery, an important setting for severe hemorrhage. Tragically, we have identified a number of recent instances of inadvertent intrathecal administration of tranexamic acid instead of local anesthetic for spinal anesthesia. Reported cases of this catastrophic error seem to be increasing. The profound neurotoxicity of tranexamic acid causes rapid‐onset convulsions, with mortality of 50%. How can these tragic errors be averted? Drug safety alerts have been issued by the US Food and Drug Administration and the World Health Organization, but that is not enough. We recommend extensive dissemination of information to raise awareness of this potential hazard, and local hospital protocols to ensure that tranexamic acid is stored separately from anesthetic drugs, preferably outside the operating room and with an auxiliary warning label. Implementation of safety strategies on a very large scale will be needed to ensure that the life‐saving potential of tranexamic acid is not eclipsed by drug‐error mortality.